Interface engineered Ca–Co mixed oxide heterostructures for boosting the aerobic and solvent-free selective oxidation of ethybenzene. (15th January 2023) - Liu, Jiangyong; Luo, Anqi; Wang, Lixia; Jian, Panming; Yan, Xiaodong
Graphical abstract: Highlights: Ca–Co mixed oxide with abundant strongly interacting heterointerfaces were obtained. The catalyst is efficient in the aerobic and solvent-free selective oxidation of ethybenzene. The interface engineering strategy contributes to the modulation of microenvironment. The Cax Coy Oz catalyst also exhibits good recyclability and high stability. This study provides a paradigm for the green oxidation of ethybenzene and beyond. Abstract: Exploration of a high-performance, low-cost and easy-to-prepare solid catalyst is a permanent goal to advance the selective oxidation of hydrocarbons to high-value-added oxygenated products. Herein, we demonstrated for the first time that Ca–Co mixed oxide with abundant strongly interacting heterointerfaces for advanced ethylbenzene oxidation performance under solvent-free conditions and using molecular oxygen as the only oxidant. The interface engineering strategy contributes to the formation of weakened Co–O bonds, enhanced oxygen vacancy concentration and boosted reactivity of lattice oxygen, facilitating the generation of superoxide radical anions for driving the ethylbenzene (EB) oxidation catalysis. In addition, the Cax Coy Oz catalyst exhibits good recyclability and high stability. This study provides a paradigm for the rational construction of metal oxides with hybrid interfaces towards a lab as well as a large-scale green oxidation of EB and beyond.